Álgebra ou geometria? Vamos a questão ! - Gomes, Ricardo César da Silva (2016)
The present work has as its theme: Algebra or Geometry? Let the question! This study discusses mainly the relationship between these two distinct areas of the curriculum perspective, basic education. The goal is to show how tenuous, and at the same fruitful time, the border that separates the basic algebra and plane geometry, and how the teacher should investigate this boundary in the very first year of high school, even before submitting Analytic Geometry. This study is organized in the form of chapters, covering the following topics in order: why the mathematics teaching, the method used in problem solving as a process, the theoretical assumption, highlighting the similarity of triangles, the Pythagorean theorem, the laws of sines and cosines, the Ptolemy's theorem, and the list of proposed issues and an epistemological discussion of the proposed problems. The work was in the light of theoretical proposals Elon Lages Lima, Terence Tao and Paulo Freire, the latter a master of pedagogy. The survey was conducted exploratory and bibliographic way, qualitative character. Finally, the study aims to clarify that the curriculum division of mathematics classrooms in primary school in Algebra and Geometry is only one curriculum division and should not affect the view that all the contents studied are part of a whole perfectly consistent; given that, being on a math problem, students and teachers can make use of both tools of algebra as geometry of the results to solve it.